1987
DOI: 10.1128/jb.169.2.856-863.1987
|View full text |Cite|
|
Sign up to set email alerts
|

Lipopolysaccharide size and distribution determine serum resistance in Salmonella montevideo

Abstract: The survival of Salmonella montevideo during serum treatment depends on the presence of an 0 antigen (0-Ag) associated with the lipopolysaccharide molecule. In this organism, the 0 antigen is a polysaccharide composed of 0 to more than 55 subunits, each containing 4 mannose residues together with glucose and n-acetylglucosamine. We used a mutant strain of S. montevideo that smooth, enteric gram-negative bacteria is efficient, and the bactericidal C5b-9 complex is formed on the surface of such smooth cells (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 41 publications
3
94
0
Order By: Relevance
“…Although the data relate to the use of model systems, we cannot, of course, rule out the possibility that the observed effect may not be relevant to infection of humans. Nevertheless, the data on the rol::Km and rfbD::Km mutants, together with those of others using other mutants affecting LPS synthesis, show that O-antigen has a very important role in pathogenesis rather than only acting passively in the evasion of host defence mechanisms (Grossman et al, 1987;Joiner et al, 1982a,b;Liang-Takasaki et al, 1982). The data presented demonstrate that the mere presence of an O-antigen is insufficient for virulence, and that maintenance of a modal LPS O-antigen chain length distribution is essential for full virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data relate to the use of model systems, we cannot, of course, rule out the possibility that the observed effect may not be relevant to infection of humans. Nevertheless, the data on the rol::Km and rfbD::Km mutants, together with those of others using other mutants affecting LPS synthesis, show that O-antigen has a very important role in pathogenesis rather than only acting passively in the evasion of host defence mechanisms (Grossman et al, 1987;Joiner et al, 1982a,b;Liang-Takasaki et al, 1982). The data presented demonstrate that the mere presence of an O-antigen is insufficient for virulence, and that maintenance of a modal LPS O-antigen chain length distribution is essential for full virulence.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3, respectively) of the LPS molecules in the low-molecular-weight population and 30 to 50% in the high-molecular-weight fractions (36,48). It (47), antibiotic susceptibility (la, 4, 18), LPS aggregate structure (47), bacteriophage recognition (25,27), immunochemical characterization (8,9,49), virulence (11,50), protection against the bactericidal action of serum (21,41), polyclonal B cell aativation, and macrophage cytotoxicity (43). The low level of LPS on P. aeruginosa that contains a long 0 polymer, however, may be sufficient to form a uniform cover over the cell, since the surface is inaccessible to rough-core-specific monoclonal antibodies (52).…”
Section: Discussionmentioning
confidence: 99%
“…The O-Ag chain length was previously correlated with bacterial virulence in mice as well as resistance to phagocytosis, cationic peptides and iron (Burns & Hull, 1998;Joiner, 1985;Skurnik & Bengoechea, 2003). Furthermore, several studies have determined that in Salmonella the O-Ag is involved in resistance to the bactericidal activity of serum complement (Grossman et al, 1987;Joiner, 1985;Tomás et al, 1988). Murray et al (2005) reported enhanced survival of bacteria in serum when the VL O-Ag was increased by previous exposure to inactivated pig serum or iron limitation; however, this effect could not be correlated with change in the expression of the wzz fepE gene.…”
Section: Introductionmentioning
confidence: 99%